Examining Risk Disclosures in Annual Reports of Banks - Sodipo, Olubunmi (2011)
This dissertation examined risk disclosure in annual reports of sample banks using content analysis. Risk disclosure was examined using Basel II pillar 3 framework of categorizing risks which is seen as salient to the banking sector. My analysis shows a positive relationship between risk disclosures and banks’ size among the sampled banks which is consistent with previous literatures that tested for this effect, relationship between risk level and quantity of disclsosures is not clearly established and further research is suggested. I also observe an increase in quantity of risk disclosure over the years same cannot be said about the quality. This research also proposed researchable areas for the future to help in the journey towards transparency and accountability.